The far-reaching implications of Montgomery for risk disclosure in practice. Issue 1 (February 2019) - Devaney, Sarah; Purshouse, Craig; Cave, Emma; Heywood, Rob; Miola, José; Reinach, Nina
The UK Supreme Court held in Montgomery v Lanarkshire HB (2015) that practitioners must take reasonable care to ensure patients are aware of any material risks involved in treatment. We reviewed all court decisions since Montgomery which deal with the case, to establish how this judgment is being interpreted by the courts and the implications of this for risk disclosure in practice. We found that Montgomery's application has been expanded in a number of ways: information about reasonable alternatives includes the provision of information about their risks and benefits; Montgomery applies to post- as well as pre-operative disclosure; and the timing of discussion with patients about risks is important. Conversely, there is evidence that the parameters of Montgomery are being curtailed, giving rise to questions about judicial commitment to patient autonomy. In some cases there is focus on the objective risks of procedures as opposed to patients' subjective concerns; in others, causation of injury is sometimes a factor that will defeat claims. There are also further questions about whether patients now should accept more responsibility for the outcome of decisions they make. We conclude that practitioners engaged in discussions about the risks of proposed treatments and their alternatives have been left in a position of uncertainty by the courts in relation to the obtaining of informed consent in practice. It is now critical that updated guidance is provided by the UK General Medical Council to give practitioners and service providers confidence that they are adhering to the law.